2017
DOI: 10.1016/j.ajhg.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Spliceosome Component CWC27 Cause Retinal Degeneration with or without Additional Developmental Anomalies

Abstract: Pre-mRNA splicing factors play a fundamental role in regulating transcript diversity both temporally and spatially. Genetic defects in several spliceosome components have been linked to a set of non-overlapping spliceosomopathy phenotypes in humans, among which skeletal developmental defects and non-syndromic retinitis pigmentosa (RP) are frequent findings. Here we report that defects in spliceosome-associated protein CWC27 are associated with a spectrum of disease phenotypes ranging from isolated RP to severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 56 publications
2
61
0
Order By: Relevance
“…ciliopathies. Consistent with this possibility, the peptidyl-prolyl isomerase Cwc27 was a hit in our 10 screen and was recently identified as a retinitis pigmentosa (RP) gene 47 . Although this syndrome 11…”
Section: Identification Of Novel Disease Genessupporting
confidence: 67%
“…ciliopathies. Consistent with this possibility, the peptidyl-prolyl isomerase Cwc27 was a hit in our 10 screen and was recently identified as a retinitis pigmentosa (RP) gene 47 . Although this syndrome 11…”
Section: Identification Of Novel Disease Genessupporting
confidence: 67%
“…Also, some non-snRNP splicing factors such as DHX38 and CWC27 have been reported associated with arRP. 14,15 The reason as to why mutation in these general splicing factors causes retinal restricted disease is unknown. One explanation might be that the retina has an extensive protein turnover (10% of photoreceptor outer segments renew daily) and a high alternative splicing rate, and are more sensitive than other tissues to disturbance in splicesome assembly.…”
mentioning
confidence: 99%
“…21 The other element of this complex is CWC27 and retinal degeneration is attributed to the dysregulation of CWC27. 22 Gene ontology revealed that the negative regulation of non-motile cilium assembly, the negative regulation of transforming growth factor beta activation, alphatubulin acetylation, and histamine-induced gastric acid secretion are the 4 major terms which are related to the 13 critical DEGs. It is reported that exposure to LAN mostly affects the body's metabolism.…”
Section: Dhx30mentioning
confidence: 99%